Pengaruh Budaya Organisasi, Komitmen Organisasional, Dan Leader Member Exchange Terhadap Organizational Citizenzhip Behavior - Arifin, Nurul; Prayekti, Prayekti; Chandra Kirana, Kusuma (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
This study aims to determine the effect of organizational culture, organizational commitment, and LMX on OCB at Balai Yasa Yogyakarta. This quantitative research uses accidental sampling technique with a sample size of 120 respondents. Data were collected using a questionnaire processed using multiple regression and classical assumptions. The findings of this study indicate that (1) organizational culture has a positive and significant effect on OCB. (2) Organizational commitment has a positive and significant effect on OCB. (3) Leader member exchange has a positive and significant effect on OCB. (4) Organizational culture, organizational commitment, and leader member exchange simultaneously have a positive and significant effect on OCB. In conclusion, organizational culture, organizational commitment, leader member exchange have a positive and significant effect on OCB of Balai Yasa Yogyakarta. Leaders can increase OCB in accordance with the discussion.